2014
DOI: 10.1016/j.compositesa.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Variable-stiffness composite panels: Defect tolerance under in-plane tensile loading

Abstract: Automated Fiber Placement is being extensively used in the production of major composite components for the aircraft industry. This technology enables the production of tow-steered panels, which have been proven to greatly improve the structural efficiency of composites by means of in-plane stiffness variation and load redistribution. However, traditional straightfiber architectures are still preferred. One of the reasons behind this is related to the uncertainties, as a result of process-induced defects, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…When plies are oriented at 90°, the fibre waviness causes a drop in properties. More recently, Falco et al [19] studied the effect of fibre angle discontinuities on the un-notched and open-hole tensile strength of quasi-isotropic laminates. Observation of the geometry of embedded defects and the resulting mechanical behaviour showed that the influence of gaps was more significant when staggering rules (offsetting of the defects in successive plies) were not applied.…”
Section: Introductionmentioning
confidence: 99%
“…When plies are oriented at 90°, the fibre waviness causes a drop in properties. More recently, Falco et al [19] studied the effect of fibre angle discontinuities on the un-notched and open-hole tensile strength of quasi-isotropic laminates. Observation of the geometry of embedded defects and the resulting mechanical behaviour showed that the influence of gaps was more significant when staggering rules (offsetting of the defects in successive plies) were not applied.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the realization that defects have a more pronounced effect on laminate resistance than on toughness. Moreover, the staggering of plies can largely reduce the effect of defects in un-notched VSP composites [27]. The influence of defects on the impact damage tolerance of steered laminates was found to be relevant only for very low impact energies [28].…”
Section: Fiber-steering For Improved Composite Performancementioning
confidence: 99%
“…The angle between adjacent courses determines the shape and size of the resulting gaps and overlaps [22]. Within the transitions zones of gaps and overlaps (transition from pristine to defective laminate) fiber angle deviations and fiber waviness may occur [48,51,69,[71][72][73][74][75][76]. The imperfection size is the determining factor for the formation of fiber waviness [48,56,57,71,77].…”
Section: Type Iv-gap and Overlapmentioning
confidence: 99%